Gatewood : Kentucky's uncommon man - Strandmark, Matthew (Kentucky remembered., 2023)
"When Louis Gatewood Galbraith passed away in 2012, the flood of tributes honoring him merely scratched the surface of the life of this colorful and controversial figure. Throughout his political career, regional and national media outlets focused on the policy ideas and public acts that made Gatewood a cultural fixture: public demonstrations, an affinity for recreational drug use, unfiltered language, and recurring political campaigns. Best known as an advocate for the legalization of cannabis, Second Amendment rights, and smaller government, Gatewood was a perennial candidate whose once-quixotic platform might have found traction in contemporary Kentucky politics. In Gatewood: Kentucky's Uncommon Man, Matthew Strandmark weaves together personal stories, public records, and oral history interviews to provide a comprehensive overview of the life and career of an eccentric and fascinating figure. From his ailment-plagued childhood in Carlisle, Kentucky, to his young adulthood spent at the fringes of Lexington society, the opening chapters of Gatewood's life were vital in developing the values that later came to define his political career--his passion for rural communities and low tolerance for bullies. As a college dropout in the 1960s, Gatewood explored both conventional and unconventional avenues of self-discovery before returning to the University of Kentucky, where he graduated from law school and found his calling as an evangelist for cannabis legalization. His appetite for the spotlight and his penchant for standing up for the underdog launched Gatewood into a thirty-year career of campaigning, groundbreaking legal cases, public activism throughout the commonwealth--and friendships with celebrities, including Woody Harrelson, Jack Herer, and Willie Nelson. As an attorney, activist, author, father, friend, and opponent, Galbraith wore many hats--and not just his beloved fedora. This revealing biography features insightful conversations with Gatewood's family and colleagues, as well as commentary from Paul E. Patton, Ernie Fletcher, Andy Barr, Ben Chandler, and other well-known Kentuckians. Gatewood provides a richer and nuanced understanding of a generous, complicated, and flawed public figure who devoted his life to helping others and whose legacy will continue to resonate with Kentuckians for generations to come"--